Molecular epidemiology - Carrington, Mary (Oxford University Press, 2001)
Provides a broad overview of the diverse approaches encompassed by the emerging discipline of molecular epidemiology. Concepts and methods at the forefront of infectious disease studies are discussed along with recent advances in studying host genetics, methods for the detection of mutations and polymorphisms, the relationship between pathologies and immune system genetics, and the use of DNA sequence information to garner insights into the evolution of infectious pathogens. The evolution and function of the immune system and a synopsis of general epidemiological design and analysis are included